Theological reflections on donation after circulatory death: the wisdom of Paul Ramsey and Moshe Feinstein - Jotkowitz, A. (Journal of medical ethics, 2008)
Due to the worldwide shortage of organs for transplantation, there has been an increased use of organs obtained after circulatory death alone. A protocol for this procedure has recently been approved by a major transplant consortium. This development raises serious moral and ethical concerns. Two renowned theologians of the previous generation, Paul Ramsey and Moshe Feinstein, wrote extensively on the ethical issues relating to transplantation, and their work has much relevance to current moral dilemmas. Their writings relating to definition of death, organ transplantation and the care of the terminally ill are briefly presented, and their potential application to the moral problem of organ donation after circulatory death is discussed.